Towards a code of ethics for community psychology and community practice in the Arab world: Defining ethical values - Abdelzaher, Fatema Abouelela (AUC Knowledge Fountain, 2018)
In response to the need for ethical guidance in Arab community psychology and other forms of community practice, this thesis used mixed methods to explore the ethical values that are of relevance to community psychologists and other community practitioners in the Arab World. A total of 18 community practitioners in the Arab region were interviewed to share their views on the importance of Arab societal values, the values of community psychology, and the principles identified in globally dominant codes of ethics for psychologists in community practice in the Arab world. Using thematic analysis, 53 themes were identified in the collected qualitative data, portraying the most important and influential values in Arab community practice. Moreover, 211 community practitioners in the Arab world responded to a self-administered questionnaire on the extent to which certain values are beneficial or problematic for Arab community practice. Descriptive statistics were used to analyze the questionnaire, identifying the most beneficial values, controversial values and values that were sometimes viewed as irrelevant to Arab community practice. Based on the interview and questionnaire data, a list of recommended ethical values for Arab community practice is identified. Since codes of ethics are built on values, the results of this research are the first step towards building a comprehensive and culturally relevant code of ethics for community practitioners, including community psychologists, in the Arab region.